People's School: Educational Equalization Strategy and Pedagogical Significance in Indonesia - Rahma Amalia; Isma Mahfiroh (Journal of Smart Pedagogy and Education, 2025)
This study examines the social and pedagogical significance of the Sekolah Rakyat program launched by the Indonesian government in 2024–2025 as a comprehensive strategy to expand educational access for marginalized communities. Using qualitative documentary analysis, this research explores policy documents, media reports, and scholarly literature to understand how the program effectively addresses structural inequality. The findings reveal that Sekolah Rakyat significantly strengthens social capital, promotes distributive justice, and cultivates critical consciousness through contextual and dialogic learning approaches. The program aligns theoretically with Rawls' principle of justice, Freire's critical pedagogy, and Bourdieu's social capital concept. However, implementation faces significant challenges related to infrastructure limitations, teacher preparedness, and public perception. These constraints underscore the critical need for robust institutional support and meaningful community engagement to ensure program sustainability and long-term effectiveness. Overall, Sekolah Rakyat demonstrates considerable potential as a transformative community-based education model that bridges educational gaps and empowers disadvantaged social groups.